The Disappearance of Yugoslavia on the Market of Global Capital Opinion/Review - Stanković Pejnović, Vesna R. (Sociološki pregled, 2019)
The process of the disintegration of Yugoslavia is a direct result of modern capitalism and its unfettered market expansion in economic terms and neoliberalism in the ideological sense. The fragmentation of Yugoslavia became a precondition for the globalization of its markets and the seizure of its wealth. Global fnancial forces are directly related to the weakening and disappearance of the state on the basis of the neoliberal model and the universalization of neoliberal discourse, which require changes in the ruling forms of the state, redefning its sovereignty through structural changes. Trough the dominance of the global fnancial system, the Western powers, in search of national and collective strategic interests, helped the Yugoslav economy to collapse and instigated its citizens to ethnic and social conﬂicts. Global media have been advocating the “free market” as the basis for rebuilding a war shattered economy. Trough the social and political inﬂuence of economic restructuring in Yugoslavia, collective understanding, social cohesion and the common Yugoslav identity gradually eroded. The intellectual and political elite dogmatically represented cultural, ethnic and religious divisions as the only cause of war and destruction. The aim of this paper is to prove that Yugoslavia has disappeared by the power of capital, through a corporate system that, through its diagrammatic structures of dispersed power based on manipulation and neoliberal ideology, managed to realize its goal of total privatization of all that belonged to the area of public goods. Keywords: Yugoslavia, global market, manipulation, ideologization, capital